Bone Marrow Concentrate Mesenchymal Stromal Cells Do not Correlate With Nucleated Cell Count or Colony Forming Units - Marta Cercone; Michelle R. Greenfield; Lisa A. Fortier (Elsevier, 2021)
Introduction: Bone marrow aspirate concentrate (BMC) is a point-of-care biologic for cartilage repair and treatment of osteoarthritis. BMC contains mesenchymal stromal cells (MSCs) which are technically difficult to measure, and therefore the extent to which they influence joint restoration is unknown. Nucleated cell count (NCC) and colony forming units (CFUs) have been proposed as surrogate markers to quantify MSCs in BMC. Objectives: The purpose of this study was to test this assumption. We hypothesized that neither NCC nor CFUs would correlate with MSCs quantity in BMC. Methods: Bone marrow was aspirated from the sternum of horses and centrifuged to obtain BMC. Aspirates were processed and automated complete blood counts were obtained on each BMC sample to obtain NCC. Samples were plated in different volumes, each in duplicate and cultured for up to 21 days when CFUs were counted. For each duplicate culture, one plate was stained with crystal violet, and adherent cells on the other plate, presumptive MSCs, were lifted, counted, and used for trilineage differentiation. Results: There was none, or a very weak correlation between NCC and CFUs, NCC and MSCs, and CFUs and MSCs. These results indicate that neither NCC nor CFUs are suitable surrogate measurements of MSCs in BMC. Conclusions: It is important to characterize biologics such as BMC so that success or failure can be attributed to a specific cellular or bioactive protein composition. Until a simple method to quantify MSCs in BMC is identified, more advanced laboratory techniques such as flow cytometry should be used in laboratory and clinical studies.